DEBUNKING THE MYTH OF ISLAMIC PARTIES: Political Ideology and Electoral Contestation in Indonesia during the Lead-up to the 2024 Election (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
This article discusses the electoral contestation and eventual defeat of Islamic parties in Indonesia's past 2024 general election. Data for this article were collected using a mixed-methods approach. Field research was conducted by the authors between March and June 2022. In addition, the authors also collected data from articles written in various national and international journals, as well as official government offices. Collected data were subsequently analyzed using the perspectives of political sociology and gender justice. Islamic parties and nationalist parties sought to gain the votes of Indonesia's Muslim-majority population by raising such issues as women, education, poverty, and the revival and survival of Islam both at home and abroad. This article also argues that the future of Indonesian Islam lies in two civil society organizations, Muhammadiyah and Nahdlatul Ulama, which represent the moderate Islam. Political Islam, conversely, relies on an essentialist understanding of Islam to attract voter support. Islamic parties do not share a clear political ideology, nor do religious-nationalist parties.